Cyclin-Dependent Kinase 4/6 Inhibitor (Palbociclib) Induced Aplastic Anemia in a Patient with Metastatic Breast Cancer - Nwabudike, Stanley Madu; Edwards, Camille V.; Akinboro, Oladimeji; Quinn, Kathryn; Sarosiek, Shayna; Ko, Naomi (Case Reports in Hematology, 2018)
Breast cancer is the most common cancer diagnosed in women worldwide. Over the years, breast cancer treatment has undergone revolutionary changes especially for women with hormone receptor positive metastatic disease. As a result, women are living longer with their disease, particularly in developed countries. The use of cyclin-dependent kinase (CDK) 4/6 inhibitors with antiestrogen therapy is a relatively new therapeutic option which has been shown to improve progression-free survival. Hematologic adverse events, most frequently neutropenia, are well-known side effects of CDK 4/6 inhibitors. However, to our knowledge, aplastic anemia has never been reported. We report a case of aplastic anemia in a patient with metastatic breast cancer treated with palbociclib after multiple prior lines of therapy.